Adult‐onset diagnosis of urea cycle disorders: Results of a French cohort of 71 patients. Issue 5 (7th June 2021) - Toquet, Ségolène; Spodenkiewicz, Marta; Douillard, Claire; Maillot, François; Arnoux, Jean‐Baptiste; Damaj, Lena; Odent, Sylvie; Moreau, Caroline; Redonnet‐Vernhet, Isabelle; Mesli, Samir; Servais, Aude; Noel, Esther; et al.
Abstract: Urea cycle disorders (UCD) are rare diseases that usually affect neonates or young children. During decompensations, hyperammonemia is neurotoxic, leading to severe symptoms and even coma and death if not treated rapidly. The aim was to describe a cohort of patients with adult onset of UCDs in a multicentric, retrospective and descriptive study of French adult patients with a diagnosis after 16 years of age of UCDs due to a deficiency in one of the 6 enzymes (arginase, ASL, ASS, CPS1, NAGS, OTC) or the two transporters (ORNT1 or citrin). Seventy‐one patients were included (68% female, 32% male). The diagnosis was made in the context of (a) a metabolic decompensation (42%), (b) family history (55%), or (c) chronic symptoms (3%). The median age at diagnosis was 33 years (range 16‐86). Eighty‐nine percent of patients were diagnosed with OTC deficiency, 7% CPS1 deficiency, 3% HHH syndrome and 1% argininosuccinic aciduria. For those diagnosed during decompensations (including 23 OTC cases, mostly female), 89% required an admission in intensive care units. Seven deaths were attributed to UCD—6 decompensations and 1 epilepsy secondary to inaugural decompensation. This is the largest cohort of UCDs diagnosed in adulthood, which confirms the triad of neurological, gastrointestinal and psychiatric symptoms during hyperammonemic decompensations. We stress that females with OTC deficiency can be symptomatic. With 10% of deaths in this cohort, UCDs in adults remain a life‐threatening condition. Physicians working in adult care must be aware of late‐onset presentations given the implications for patients and their families.